2016
DOI: 10.1371/journal.pone.0155340
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming the Refractory Expression of Secreted Recombinant Proteins in Mammalian Cells through Modification of the Signal Peptide and Adjacent Amino Acids

Abstract: The expression and subsequent purification of mammalian recombinant proteins is of critical importance to many areas of biological science. To maintain the appropriate tertiary structure and post-translational modifications of such proteins, transient mammalian expression systems are often adopted. The successful utilisation of these systems is, however, not always forthcoming and some recombinant proteins prove refractory to expression in mammalian hosts. In this study we focussed on the role of different N-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 24 publications
3
45
0
Order By: Relevance
“…The secretion function has been conserved from bacteria through eukaryotes and, though diverse in length/composition, ss share a conserved tripartite structure: 20-30 residues in length with a basic "N domain," a 7-13 residue hydrophobic "H domain" and a slightly polar "C domain." 18 In addition to this common structure, conservation of residues in particular positions of the mammalian signal peptide sequences is emerging. In this sense, our results are corroborated by very recent findings showing that in mammalian ss, small neutral amino acids are prevalent in ¡1 (last amino acid of the signal peptide) and ¡3 positions, whereas bulky aromatic amino acids are often found at ¡2 position and proline residues are virtually absent from all positions from ¡3 to C1 (first amino acid of the mature peptide) positions.…”
Section: Discussionmentioning
confidence: 99%
“…The secretion function has been conserved from bacteria through eukaryotes and, though diverse in length/composition, ss share a conserved tripartite structure: 20-30 residues in length with a basic "N domain," a 7-13 residue hydrophobic "H domain" and a slightly polar "C domain." 18 In addition to this common structure, conservation of residues in particular positions of the mammalian signal peptide sequences is emerging. In this sense, our results are corroborated by very recent findings showing that in mammalian ss, small neutral amino acids are prevalent in ¡1 (last amino acid of the signal peptide) and ¡3 positions, whereas bulky aromatic amino acids are often found at ¡2 position and proline residues are virtually absent from all positions from ¡3 to C1 (first amino acid of the mature peptide) positions.…”
Section: Discussionmentioning
confidence: 99%
“…To determine predicted cleavage sites and relative "signal peptide-ness" (D-scores), each synthetic signal peptide was screened in silico using SignalP 4.1 (www.cbs.dtu.dk/services/SignalP ;Petersen, Brunak, von Heijne, & Nielsen, 2011). Güler-Gane et al (2016) recently showed that the secretion efficiency of recombinant proteins can be generally increased by inserting two alanine residues at the signal peptidemature protein junction, and accordingly this design feature was added to all five synthetic components (see Supporting Information Table S1 for sequences). Güler-Gane et al (2016) recently showed that the secretion efficiency of recombinant proteins can be generally increased by inserting two alanine residues at the signal peptidemature protein junction, and accordingly this design feature was added to all five synthetic components (see Supporting Information Table S1 for sequences).…”
Section: Signal Peptidesmentioning
confidence: 99%
“…The performance of signal peptide parts is typically unpredictable as the design rules governing their function are poorly defined (Brockmeier et al, 2006;Haryadi et al, 2015;Obst, Lu, & Sieber, 2017). For this example, such screening was unnecessary as previous studies have already identified an appropriate signal peptide for the specific context of SEAP production in mammalian cells (Barash et al, 2002;Güler-Gane et al, 2016). Moreover, it is not known why signal peptide function is highly protein-specific, a phenomenon that is likely determined by amino acid sequences at the signal peptide-product N-terminal junction.…”
Section: Protein Translocationmentioning
confidence: 99%
See 2 more Smart Citations